Estimating the non-monetary burden of neurocysticercosis in Mexico. - Rachana Bhattarai; Christine M Budke; Hélène Carabin; Jefferson V Proaño; Jose Flores-Rivera; Teresa Corona; Renata Ivanek; Karen F Snowden; Ana Flisser (Public Library of Science (PLoS), 2012)
BACKGROUND: Neurocysticercosis (NCC) is a major public health problem in many developing countries where health education, sanitation, and meat inspection infrastructure are insufficient. The condition occurs when humans ingest eggs of the pork tapeworm Taenia solium, which then develop into larvae in the central nervous system. Although NCC is endemic in many areas of the world and is associated with considerable socio-economic losses, the burden of NCC remains largely unknown. This study provides the first estimate of disability adjusted life years (DALYs) associated with NCC in Mexico. METHODS: DALYs lost for symptomatic cases of NCC in Mexico were estimated by incorporating morbidity and mortality due to NCC-associated epilepsy, and morbidity due to NCC-associated severe chronic headaches. Latin hypercube sampling methods were employed to sample the distributions of uncertain parameters and to estimate 95% credible regions (95% CRs). FINDINGS: In Mexico, 144,433 and 98,520 individuals are estimated to suffer from NCC-associated epilepsy and NCC-associated severe chronic headaches, respectively. A total of 25,341 (95% CR: 12,569-46,640) DALYs were estimated to be lost due to these clinical manifestations, with 0.25 (95% CR: 0.12-0.46) DALY lost per 1,000 person-years of which 90% was due to NCC-associated epilepsy. CONCLUSION: This is the first estimate of DALYs associated with NCC in Mexico. However, this value is likely to be underestimated since only the clinical manifestations of epilepsy and severe chronic headaches were included. In addition, due to limited country specific data, some parameters used in the analysis were based on systematic reviews of the literature or primary research from other geographic locations. Even with these limitations, our estimates suggest that healthy years of life are being lost due to NCC in Mexico.